2016
DOI: 10.1111/and.12551
|View full text |Cite
|
Sign up to set email alerts
|

Determining the need for rescue intracytoplasmic sperm injection in partial fertilisation failure during a conventional IVF cycle

Abstract: To explore the need for rescue intracytoplasmic sperm injection (ICSI) in cases of partial fertilisation failure during a conventional in vitro fertilisation cycle, rescue ICSI was performed for cycles with a fertilisation rate of <50%. The data were divided into three groups based on the fertilisation rate: group 1 (0%), group 2 (<25%) and group 3 (>25%). The impact of rescue ICSI on each group was then analysed in terms of ovum fertilisation, embryo development, embryo utilisation and selection of embryos fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
0
6
4
Order By: Relevance
“…In terms of embryo development after rescue ICSI performed based on the second polar body extrusion rate, Cao et al reported that the higher the second polar body extrusion rate, the lower the blastocyst development rate. 14 In our study, however, the blastocyst development and implantation rates did not decrease in cycles with a second polar body extrusion rate of ≥50%, indicating that the expansion of rescue IVF indications does not exert a negative effect on embryo development.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…In terms of embryo development after rescue ICSI performed based on the second polar body extrusion rate, Cao et al reported that the higher the second polar body extrusion rate, the lower the blastocyst development rate. 14 In our study, however, the blastocyst development and implantation rates did not decrease in cycles with a second polar body extrusion rate of ≥50%, indicating that the expansion of rescue IVF indications does not exert a negative effect on embryo development.…”
Section: Discussioncontrasting
confidence: 53%
“…Early rescue ICSI is indicated for cases suspected of TFF, in which not even a single oocyte from which a second polar body has been extruded 4–8 h after insemination is obtained. 6 , 7 , 8 , 9 , 10 , 11 , 12 Although studies reported that rescue ICSI was performed in cases where the second polar bodies had been extruded from some oocytes, 13 , 14 , 15 , 16 they targeted cases in which the ratio of oocytes from which the second polar bodies had been extruded was <50%. It is expected that many unfertilized oocytes can be saved, but a study reported a high polyspermy rate in rescue ICSI performed in cases with an IVF fertilization rate of >25%, 14 thus raising concerns that unnecessary rescue ICSI may be performed if the indications are expanded.…”
Section: Introductionmentioning
confidence: 99%
“…In partial fertilization failure, rescue ICSI more often leads to polyploidy, considering the delayed timing of fertilization or the presence of fragmented PB, along with the occurrence of pseudo double polar bodies. Consequently, rescue ICSI is not recommended for patients with conventional IVF rates of >25%, as it is associated with high risks and low returns (7).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the presence of fragmented PBs and pseudo double PBs makes identification more complicated, especially in cases of partial fertilization failure. Thus, early-rescue ICSI tends to lead to a higher rate of polyploidy (7).…”
mentioning
confidence: 99%
“…The last topic of interest is whether r-ICSI should be performed on all oocytes without fertilization at 6 hr after coincubation. A recent study reported that r-ICSI is only recommended for cases with IVF fertilization rates <25%, considering the risk of artificial 3PN zygote in cases with IVF fertilization rates >25% ( 18 ). In the present study, in the comparison between the six- hr and r-ICSI groups, the 2PB rates at 6 hr after insemination were 43.6% and 11.6%, respectively, indicating a distinct fertilization disorder in the r-ICSI group.…”
Section: Discussionmentioning
confidence: 99%